2011
DOI: 10.4161/chim.17917
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric bone marrow as potential source of hematopoietic stem cells for transplantation

Abstract: Every year, bone marrow transplantation saves many lives worldwide. Unfortunately, a suitable donor is not always available. Since organs are routinely harvested from cadaveric organ donors, we decided to assess such a possibility for bone marrow. We analyzed the functional properties and phenotypic markers of murine hematopoietic stem and progenitor cells (HSPC) from cadaveric bone marrow and during storage in vitro in a suspension. It was demonstrated that HSPC exposed to a warm or cold ischemia in intact fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…These quiescent or dormancy stem cells survive by adapting to low oxygen consumption with a slow metabolism and no transcription program [23]. The isolation of viable and functional cadaveric stem cells from human bone marrow [24,25], brain [10,26] and muscle [12] up to many days postmortem is possible today, but cadaveric cryopreserved vessels remain unstudied.…”
Section: Discussionmentioning
confidence: 99%
“…These quiescent or dormancy stem cells survive by adapting to low oxygen consumption with a slow metabolism and no transcription program [23]. The isolation of viable and functional cadaveric stem cells from human bone marrow [24,25], brain [10,26] and muscle [12] up to many days postmortem is possible today, but cadaveric cryopreserved vessels remain unstudied.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that human pluripotent haematopoietic stem cells could survive in cadaveric bone marrow(BM). [17][18][19] It has also been shown previously that split-thickness skin grafts could be allografted up to 3 weeks after death if stored at 4 C. 20 More recently, stem and adult cells have been isolated from post mortem brain, spinal cord, and retinal tissue. 3,[21][22][23] These findings showed that, due to the persistence of stem cells, cadaver tissue could be a potential abundant source of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…When quality, as measured by colonyforming units, of CD marrow is compared with bone marrow aspirated from LD, they saw a tendency towards lower amounts in the cadaveric marrow, but the difference was not significant. As regards of costs, the method for harvesting and procurement of cadaveric bone marrow was relatively simple and fast, when used together with organ retrieval [11,12]. In 1986 a 12 year old male with acute lymphocytic leukemia received donor bone marrow from his histocompatible father whose marrow was harvested 40 minutes postmortem after he suffered a myocardial infarction.…”
Section: Bone Marrow and Other Cadaver Sites For The Obtention Of Viamentioning
confidence: 99%
“…Recent studies have shown that CBM cells could be stored up to seven days without an increase in apoptosis and that three days of storage does not affect the CD34+ fraction of the cells. The bone marrow could be harvested in case of a sudden death, phenotyped and transplanted immediately or stored for later use [12]. Neurosphere-generating cells can be isolated from adult mouse spinal cord and forebrain subependymal zone after postmortem intervals of up to 140 h, when kept at 4°C, and up to 30 h when kept at room temperature.…”
Section: Surviving Times Of Cscsmentioning
confidence: 99%
See 1 more Smart Citation